Preoperative assessment of factors associated with difficulty in performing total laparoscopic hysterectomy. Issue 2 (February 2017) - Saito, Ako; Hirata, Tetsuya; Koga, Kaori; Takamura, Masashi; Fukuda, Shinya; Neriishi, Kazuaki; Pastorfide, Gia; Harada, Miyuki; Hirota, Yasushi; Wada‐Hiraike, Osamu; Fujii, Tomoyuki; Osuga, Yutaka
Abstract: Aim: Our objective was to determine the preoperative factors associated with difficulty in total laparoscopic hysterectomy (TLH). Methods: This retrospective clinical study included 157 patients who underwent TLH for leiomyoma or adenomyosis between 2009 and 2013. All patients underwent magnetic resonance imaging (MRI) before surgery. We categorized patients as 'difficult' if the operation time was > 243 min, if total blood loss was > 500 mL, or if conversion to laparotomy was necessary. Preoperative information, including MRI findings, was compared between the difficult and 'other' patients. Stepwise logistic regression analysis was used to control for covariates that were significant on univariate analysis ( P < 0.05). Results: The presence of an endometrioma, a previous cesarean section (CS), a wide uterus, and a high body mass index were independent risk factors for being a difficult patient. For adenomyosis patients, the presence of an endometrioma, a prior CS, subtype II adenomyosis, and high body mass index were independent risk factors for being a difficult patient. For leiomyoma patients, the presence of an endometrioma, a prior CS, and having at least seven leiomyomas were independent risk factors for being a difficult patient. All laparotomy conversion patients had multiple risk factors. Conclusion: We have elucidated the factors associated with difficult TLH patients using patients' background and preoperative MRI findings. Awareness of these predictive factors may enable surgeons to prepare for the operation, minimize complications, or choose another more appropriate route of hysterectomy than TLH.